(3GdLhGH GdfGWb HGdUhGH GdbGWY dYQi GdTc hGdGQJjGHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfWb dSGf GdHQgGf HMGdg hHYO ahQOJ YdfjG eSGFd ef LgI GdbGVi aQCjfG LhGHgG aQVkG s
(3BNQgG (B:s
(3hGdhba ef LgI GdeUGdM GdOjfjI adG jchf eJUQakG ajgG gPG eG CQOfG PcQg ef LhGH gPg GdeSGFd s
(3CLGH GdeDda HcJGHg Ydi GdbGVi HOQ GdOjf eMeO Hf CMeO ai eSGFd hQOJ efgs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ GdahGJM HGdSejc s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs